ANALISIS KUALITAS PELAYANAN DALAM MENINGKATKAN PENJUALAN CV BILCA TAHUN 2024-2025 - Nur Miranti; Yustina Olivia da Silva; Maria Modesta Missi Mone (Universitas Nusa Nipa Maumere, 2026)
This study aimed to analyse the impact of customer service quality on sales at CV BILCA Digital Printing in Maumere for the 2024-2025 period. Grounded in the SERVQUAL model, this qualitative research posits that the five dimensions–responsiveness, reliability, empathy, assurance, and tangibles–synergistically build customer trust, which in turn drives repeat purchases and word-of-mouth (WOM). The study involved 15 customers selected through purposive sampling. Data were collected via in-depth interviews, participant observation, and internal documentation. Analysis was conducted using the Miles & Huberman model, encompassing data reduction, display, and conclusion drawing. The findings confirm that all five SERVQUAL dimensions collectively cultivate trust, leading to increased repeat purchases and positive WOM. Key results reinforce a “Trust Chain” mechanism: response times of ≤30 minutes and on-time production foster initial trust; personalized interactions strengthen affective bonds; and robust recovery policies reduce perceived risk by exceeding expectations. Notably, no instances of customer churn were observed, as all participants made repeat orders within 24 hours of a positive experience. This study contributes to the services marketing literature by empirically validating trust as a key mediator between service quality dimensions and behavioural outcomes, while also offering a replicable empirical model for Micro, Small, and Medium–sized Enterprises (MSMEs) in the digital printing sector.